Perbaikan kualitas Citra Menggunakan Metode Gaussian Filter - Sunandar, Hery (MEANS (Media Informasi Analisa dan Sistem), 2017)
The image is in the form of variations in the intensity of a pixel that does not correlate with neighboring pixels that are easily seen by the eye because they look different. By doing image smoothing, it is expected that the image will become more visible. In certain cases, smoothing of the image is indeed done to soften the surface of the image, such as removing small details. Gaussian filter is a mask that is also often used for image smoothing is a gaussian smoothing mask. The existence of quality improvements in the image can improve the image that has very low quality with a gaussian filter.